Emotions in Crisis: Consequences of Ceremonial Refugee Camp Visits to Bhutanese Refugee Camps in Nepal - Warren, Kamryn (Refuge, 2023)
Research on refugee resettlement frequently overlooks the larger context of the experience of forced migration. As a result, the micro-level interactions between refugees and the bureaucrats who make resettlement decisions are obscured. We can better understand the socio-political dynamics between refugees and the officials deciding their resettlement cases if we approach encounters between refugees and migration officials during ceremonial visits as sites of emotional exchange. This article examines the complex socio-political emotional exchanges of power and vulnerability that underpin the refugee resettlement process through an ethnographic analysis of Bhutanese refugee camps in Nepal.